Χρήση εντομοπαθογόνων νηματωδών για τη βιολογική αντιμετώπιση των λεπιδοπτέρων εχθρών του λάχανου - Χριστοδούλου, Θεογνωσία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Cabbage (Brassica oleracea L.) is a year-round vegetable crop cultivated in Cyprus. One of the most important problems in the production of cabbage is the quantitative and qualitative damage caused to the edible part of the plant (head) by lepidopteran larvae in the families Pieridae and Noctuidae (Pieris brassicae, P. rapae, Spodoptera littoralis, and S exigua). In this dissertation, we contacted a field experiment to evaluate the effectiveness of the Entomopathogenic nematode (EPN), Steinernema carpocapsae+ hydrate buffer Biorend R, using three different doses and water as a control, against lepidopterous pests of cabbage. The effectiveness of the insecticide application was based on the percentage of marketable cabbage heads at harvest using a scale from 0 to 5 were 0 are the non-infected plants and 5 are the infected plants. Cabbage heads were scored as 4 and 5 which indicate that all cabbage heads were unmarketable. The field experiment showed that EPN’s can not be effective as biocontrol agents against lepidopterous pests of cabbage under the summer climate conditions in Cyprus, even though precautionary measures where taken to keep the nematodes moist (applications late in the afternoon and use of the hydrate buffer Biorent R). EPN’s where found alive and active in the soil around each plant two months after the last treatment, indicating that EPN’s could be used as biocontrol agents against soil insect pests.
Keywords: Τemperature; Cabbage; Θερμοκρασία; Λάχανα